Analysis of the water‐soluble compounds as a tool for discriminating traditional and industrial high moisture mozzarella made with citric acid. (16th May 2021) - Faccia, Michele; Natrella, Giuseppe; Gambacorta, Giuseppe
Abstract: High moisture mozzarella from cow milk is a pasta filata cheese that can be manufactured by different protocols. Fermentation by autochthonous starter is used for the traditional product, whereas direct acidification with citric acid is widely used at industrial level. Both types are stored immersed in a liquid for preserving freshness, but this packaging method is known to favour the changes of the quality characteristics. The present study aimed to assess the evolution of the soluble compounds and to evaluate their use as chemical indices for discriminating the two types of mozzarella. The contents of lactose, organic acids, water‐soluble nitrogen and free amino acids differently changed over time. The whole patterns of these soluble compounds allowed discrimination of the two products during the whole storage period. The simple analyses of lactic acid and lactose could be a rapid tool to protect traditional mozzarella from industrial imitations obtained with citric acid. Abstract : The soluble fraction of high moisture mozzarella can be used for discriminating the traditional product from the industrial type. The concentration of the soluble compounds tend to evolve during storage, also because the cheese is stored into a covering liquid, causing mass exchange phenomena. The most useful compounds for discrimination are lactose, lactic acid and free aminoacids.